2013
DOI: 10.1002/term.1796
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological priming of adipose-derived stem cells for paracrine VEGF production with deferoxamine

Abstract: Adipose-derived stem cells (ASCs) show great potentials in applications such as therapeutic angiogenesis, regenerative medicine and tissue engineering. Pharmacological preconditioning of stem cells to boost the release of cytoprotective factors may represent an effective way to enhance their therapeutic efficacy. In this study, the aim was to determine whether deferoxamine can enhance the release of vascular endothelial growth factor (VEGF) from in vitro expanded ASCs. It is demonstrated that deferoxamine (50-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
21
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 47 publications
4
21
1
Order By: Relevance
“…This wash-out effect is important with regards to future in vivo applications, since it indicates a prolonged effect of the in vitro priming with DFX. Similar effects of DFX preconditioning have already been reported with regard to BM-MSCs [24] and adipose-derived stem cells (ASCs) [25]. Moreover, Agis and colleagues already reported an increased VEGF secretion after treating periodontal ligament fibroblasts with DFX [11].…”
Section: Discussionsupporting
confidence: 57%
“…This wash-out effect is important with regards to future in vivo applications, since it indicates a prolonged effect of the in vitro priming with DFX. Similar effects of DFX preconditioning have already been reported with regard to BM-MSCs [24] and adipose-derived stem cells (ASCs) [25]. Moreover, Agis and colleagues already reported an increased VEGF secretion after treating periodontal ligament fibroblasts with DFX [11].…”
Section: Discussionsupporting
confidence: 57%
“…Low-dose UVB irradiation also upregulated bFGF, KGF, VEGF, and HGF, which enhanced the hair-regenerative potential of ASCs [15]. In addition, pharmacological priming of ASCs using deferoxamine induces HIF-1a and VEGF expression, and enhanced the migration and in vitro woundhealing activities of endothelial cells [47]. In the present study, we showed that vitamin C primarily increased HGF, IGFBP6, VEGF, bFGF, and KGF, which collectively enhanced the hairregenerative potential of ASCs.…”
Section: Discussionmentioning
confidence: 94%
“…The regenerative potential of ASCs and the paracrine effect of ASCs differ according to the stimulators used [12,15,[45][46][47]. For example, hypoxia upregulated VEGF and bFGF, which enhanced wound healing and hair-regenerative potential of ASCs [12].…”
Section: Discussionmentioning
confidence: 99%
“…Phamacological preconditioning of stem cells to boost the release of cytoactive factors may represent the effective way to enhance their functional efficacy (14). Our experiments indicated that the paracrine effect of ASCs was significantly augmented by stimulation of media with LL-37.…”
Section: Discussionmentioning
confidence: 99%